2001
DOI: 10.1101/gad.887301
|View full text |Cite
|
Sign up to set email alerts
|

Control of axillary bud initiation and shoot architecture in Arabidopsis through the SUPERSHOOT gene

Abstract: The aerial architecture of flowering plants is determined to a large extent by shoot growth and shoot branching arising from the initiation and growth of axillary meristems. We have identified an Arabidopsis mutant, supershoot (sps), which is characterized by a massive overproliferation of shoots, such that a single plant can generate 500 or more inflorescences. Analysis of the mutant plants shows that the primary defect is because of an increase in the number of meristems formed in leaf axils, together with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
153
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 60 publications
(67 reference statements)
13
153
1
3
Order By: Relevance
“…These mutants exhibit massive proliferation of shoots, together with other developmental defects. The quantification of hormone levels in sps/cyp79F1 mutant plants indicates that both auxin and cytokinins are higher in the mutants, but the phenotypes of the sps/cyp79F1 plants are consistent with higher levels of cytokinins rather than auxins as the key factor responsible for the change in branching pattern (Tantikanjana et al, 2001).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…These mutants exhibit massive proliferation of shoots, together with other developmental defects. The quantification of hormone levels in sps/cyp79F1 mutant plants indicates that both auxin and cytokinins are higher in the mutants, but the phenotypes of the sps/cyp79F1 plants are consistent with higher levels of cytokinins rather than auxins as the key factor responsible for the change in branching pattern (Tantikanjana et al, 2001).…”
mentioning
confidence: 88%
“…These mutants exhibit massive proliferation of shoots, together with other developmental defects. The quantification of hormone levels in sps/cyp79F1 mutant plants indicates that both auxin and cytokinins are higher in the mutants, but the phenotypes of the sps/cyp79F1 plants are consistent with higher levels of cytokinins rather than auxins as the key factor responsible for the change in branching pattern (Tantikanjana et al, 2001).Despite the fact that sps/cyp79F1 plants resemble hormone mutants, biochemical studies have shown that SPS/CYP79F1 gene encodes an enzyme catalyzing metabolism of both short-chain and long-chain elongated Met-derivatives in the biosynthesis of aliphatic glucosinolates (Hansen et al, 2001;Chen et al, 2003). Glucosinolates are a group of secondary plant metabolites known to play a role in plant defense and are sources of flavor compounds, cancer-preventing agents, and bioherbicides.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The outgrowth phenotype of the bud2 axillary buds may also result from altered cytokinin biosynthesis and/ or response, because cytokinin has long been proposed as a secondary messenger of IAA in controlling shoot branching [63][64][65]. We therefore compared the endogenous levels of various cytokinins between bud2-2 and wild-type seedlings.…”
Section: Altered Biosynthesis Of Cytokinins In Bud2 Plantsmentioning
confidence: 99%
“…Until the isolation and characterization of branching mutants in various species, it was not possible to address these issues. In recent decades, many branching mutants have been isolated that have problems with auxin, cytokinin, or brassinosteroids, for example, and show highly pleiotropic phenotypes typical for these hormones (Lincoln et al, 1990;Azpiroz et al, 1998;Tantikanjana et al, 2001). However, a class of mutants were isolated that displayed a specific increase in bud outgrowth that was not correlated with any known hormonal signal (Beveridge et al, 1996(Beveridge et al, , 1997.…”
mentioning
confidence: 99%